Akulturasi Arsitektur Istana Maimun: Representasi Penerimaan Budaya Melayu terhadap Pengaruh Asing - Ashfa Ashfiyatush Shoffiyah (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2025)
Maimun Palace, a prominent legacy of the Deli Sultanate, embodies a remarkable synthesis of diverse architectural traditions. Although numerous studies have examined Maimun Palace, most have predominantly concentrated on its historical significance and tourism potential, while scholarly investigations specifically addressing architectural acculturation as a reflection of the cultural disposition of the Malay community remain relatively limited. This study aims to analyze the forms of architectural acculturation manifested in Maimun Palace and to elucidate how the Malay community has adapted foreign cultural influences without relinquishing its indigenous cultural identity. Employing a descriptive qualitative approach, the research draws upon field observations, visual documentation, and an extensive review of relevant literature. The findings reveal that architectural acculturation is manifested through the incorporation of domes and horseshoe arches inspired by Middle Eastern and Mughal architectural traditions, symmetrical spatial arrangements as well as large doors and windows influenced by European architecture, and the predominance of yellow hues and distinctive Malay ornaments that signify local identity. These findings demonstrate that the Malay community selectively appropriated external cultural elements and creatively integrated them into local architectural forms. This study contributes to the broader discourse on architectural acculturation in Indonesia by positioning Maimun Palace as a compelling representation of the Malay community’s cultural openness to global influences while simultaneously preserving its distinctive local character